2014
DOI: 10.4314/tjpr.v13i11.23
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and anti-biofilm activity of burdock (<i>Arctium lappa</i> L Asteraceae) leaf fractions against <i>Staphylococcus aureus</i>

Abstract: Purpose: To determine the chemical composition and anti-biofilm activity of burdock leaf fractions against Staphylococcus aureus Methods: The anti-biofilm activity of burdock leaf fractions obtained by column chromatography against S. aureus was determined by minimum inhibitory concentration (MIC). Scanning electron microscopy was employed to further investigate the inhibitory activity. Analysis of the chemical composition of the fractions was performed by ultra-performance liquid chromatography-mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Two new neolignan glucosides named (70S, 80R, 8S)-4,40,90- trihydroxy-3,30-dimethoxy-70,9-epoxylignan-7-oxo-4- O -b- D -glucopyranosyl-40- O -b- D -glucopyranoside and (7S, 8R)-4,7,9,90-tetrahydroxy-3,30-dimethoxyl- 70-oxo-8-40- oxyneolignan-4- O -b- D -glucopyranoside were determined from the fruit extract of A. lappa (Yang et al, 2012). The occurrence of phenolic acids, caffeic acid, cynarin and chlorogenic acid has been reported for the first time in A. lappa seeds and leaves (Ferracane et al, 2010; Tang et al, 2014; Lou et al, 2016) and later in both seeds and roots (Predes et al, 2011). Chlorogenic acid was determined by Tardio et al (2005) in the seeds of A. lappa .…”
Section: Phytochemistrymentioning
confidence: 95%
See 1 more Smart Citation
“…Two new neolignan glucosides named (70S, 80R, 8S)-4,40,90- trihydroxy-3,30-dimethoxy-70,9-epoxylignan-7-oxo-4- O -b- D -glucopyranosyl-40- O -b- D -glucopyranoside and (7S, 8R)-4,7,9,90-tetrahydroxy-3,30-dimethoxyl- 70-oxo-8-40- oxyneolignan-4- O -b- D -glucopyranoside were determined from the fruit extract of A. lappa (Yang et al, 2012). The occurrence of phenolic acids, caffeic acid, cynarin and chlorogenic acid has been reported for the first time in A. lappa seeds and leaves (Ferracane et al, 2010; Tang et al, 2014; Lou et al, 2016) and later in both seeds and roots (Predes et al, 2011). Chlorogenic acid was determined by Tardio et al (2005) in the seeds of A. lappa .…”
Section: Phytochemistrymentioning
confidence: 95%
“…Likewise, the occurrence of quercetin-3- O -rhamnoside was reported from the leaves of A. lappa . Later, the presence of phenolic compounds such as quercetin, quercitrin, rutin, and luteolin have been reported in seeds, fruits, leaves and roots of A. lappa (Saleh and Bohm, 1971; Tamayo et al, 2000; Yu et al, 2003; Lou et al, 2010a,b, 2016; Predes et al, 2011; Liu et al, 2012; Tang et al, 2014). Also, few isoflavone derivatives including genistein, nobilein, biachanin A and tangeretin have been detected in A. lappa roots (Eberding et al, 2007).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Flavonoids present in the Arctium genus include flavones, flavonols and their glycosides. Flavonoids such as isoquercetin and rutin, which are the two main constituents, and minor ones including quercimeritrin, quercetin, quercitrin, astragalin and quercetin-3-O-rhamnoside, have been reported to be present in leaves, fruits, seeds and roots of Arctium lappa [ 194 , 195 ]. Arctigenin is widely used in traditional medicine and numerous studies have reported the therapeutic potential of this compound as an immune modulator, anti-inflammatory and antitumor agent [ 196 , 197 ].…”
Section: Arctium (Burdock)mentioning
confidence: 99%